Industrializzazione e progresso: la lezione della Rivoluzione d’ottobre - Grimaldi, Giorgio (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
Industrialization is the only way to achieve the development of the productive forces required for the opening of a more advanced historical phase, but industrialization is also the historical constitutive model of western capitalism. Marx and Engels never had nostalgia about past times, and least of all about a hypothetical peaceful state of nature, but always looked forward starting from their own times. Following this line of thinking, we will refer to Hegel’s Philosophy of Right for some observations on the nature of labor and its progressive mechanization; and will refer to Marx and Engels (Communist Manifesto; Capital; Grundrisse) for a discussion on industrialization and progress, in order to understand the huge challenge the October Revolution faced but also our contemporary philosophical and political horizon. Keywords: Industrialization; October Revolution; Technology; Marx; Hegel.